Developmental and ultrastructural characters of the pollen grains and tapetum in species of nymphaea subgenus hydrocallis - Zini, Lucía Melisa (2017)
Fil: Zini, Lucía Melisa. Consejo Nacional de Investigaciones Científicas y Técnica. Instituto de Botánica del Nordeste; Argentina.